2018
DOI: 10.1080/15421406.2018.1542104
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Kasha’s rule in higher excited states of 4-pyrilocyanines

Abstract: Spectral properties of the series of cationic polymethine dyes containing conjugated chain of different length and 4-pyrylium terminal groups were studied in details. Besides, the steadystate long-wavelength fluorescence from the lowest excited state and the fluorescence from higher excited states were experimentally revealed. The steady-state fluorescence band from the lowest excited state is shifted bathochromically with lengthening of the polymethine chain, which is also reflected in the absorption shift. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The PC dye purity of ≥ 98% was determined by liquid chromatography-mass spectrometry (LC-MS). Steady-state fluorescence studies for PC dye showed the possibility of emission excitation from higher excited states [20]. The PC dye molecule exists in the solvents dissociated into conjugated cation and counter anion (ClO 4 -).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PC dye purity of ≥ 98% was determined by liquid chromatography-mass spectrometry (LC-MS). Steady-state fluorescence studies for PC dye showed the possibility of emission excitation from higher excited states [20]. The PC dye molecule exists in the solvents dissociated into conjugated cation and counter anion (ClO 4 -).…”
Section: Methodsmentioning
confidence: 99%
“…Our group low-temperature studies of timeresolved PL emission spectra (TRES) with picosecond time resolution have shown that several radiation components can be discriminated in these spectra depending on the recording time [15]. In instantaneous TRES, emission bands can be distinguished, the maxima of which are located both on the short-wave side of the absorption band maximum (breaking Kasha's rule [20]) and on the long-wave side. These PL bands are characterized by different delay times with respect to the maximum of the exciting laser pulse and different PL lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…5 Fourth, suppression of Kasha's rule can be associated with the different nature of the S 2 and S 1 excited states, as was observed in pyrylocyanines (i.e., when one molecular orbital is totally delocalized over the polymethine chain and the other represents quasi-local states located only within the terminal groups, between which, therefore, the electronic transition in the form of IC is suppressed). 6 Other approaches that could suppress IC and the corresponding nonradiative recombination can be found from the examples of the S 1 → S 0 transition; these mechanisms can be used for promoting emission from the higher excited states too. These include suppression of electron-vibration coupling through exciton delocalization by stacking of molecules in an aggregate; 7,8 the reduction of electronic S 2 − S 1 gap nonadiabatic coupling which is qualitatively proportional to the electronic transition density, determined by the overlap between the electron and hole wave functions in the excited states; 9 and employment of intermolecular chargetransfer (CT) aggregates.…”
mentioning
confidence: 99%
“…A third mechanism that allows fluorescence from S 2 requires both favorable separation between S 2 and S 1 and symmetry-prohibited conversion between them . Fourth, suppression of Kasha’s rule can be associated with the different nature of the S 2 and S 1 excited states, as was observed in pyrylocyanines (i.e., when one molecular orbital is totally delocalized over the polymethine chain and the other represents quasi-local states located only within the terminal groups, between which, therefore, the electronic transition in the form of IC is suppressed) . Other approaches that could suppress IC and the corresponding nonradiative recombination can be found from the examples of the S 1 → S 0 transition; these mechanisms can be used for promoting emission from the higher excited states too.…”
mentioning
confidence: 99%